The Role of Islamic Financial Management in Developing the Umrah Travel Business - Novita Sari; Siti Mujiatun (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to analyze in depth the implementation and impact of sharia-based financial management on the development of the Umrah travel business at PT Zam Zam Wisata Islami. Using a qualitative method with a case study approach, data is collected through interviews, observations, and documentation. The results of the study show that PT Zam Zam Wisata Islami consistently applies sharia principles, such as the prohibition of riba, gharar, and maysir, which have proven effective in supporting business sustainability. The company also adopts a risk mitigation strategy to mitigate exchange rate fluctuations and enhance the transparency of the pilgrim fund management. The key finding is that Islamic financial management plays a vital role in building public trust, maintaining financial stability, and expanding the operational reach of the Umrah travel business.